A Brief Description on Concrete Technology (International Journal of Innovative Research in Computer Science & Technology, 2020)
Concrete is a composite material comprised  of coarse rock connected along with liquid concrete that  solidifies over the long run and is viewed as the foundation  of the structure business. Since the substantial business  polishes off 1.5 billion tons of concrete, 900 million liters  of water, and 9 million tons of sand and water every year,  there is a need to foster an option eco-accommodating  material that will keep our normal assets from being  depleted. The author of this article discusses the materials  used in concrete preparation, as well as their kinds and  testing. The primary goal of sustainable development is to  discover alternative materials that will reduce the negative  effects of the concrete industry on the environment while  also contributing to natural resource preservation. The  purpose of this article is to describe the concrete  preparation process as well as the negative effects of the  elements used in it.
Keywords: Cement; Concrete; Health; Mixture,; Water